Development of Supply Chain Risk Mitigation to Develop an Effective Strategy for Small and Medium Enterprises - Henni Henni; Diah Pramestari; Dwi Dinariana; Fitri Suryani; Siti Sujatini; Al Ikbal Arby (Research Synergy Press, 2024)
Supply chain risk management is the process of detecting, analyzing, and managing risks associated with a company’s supply chain. Risk reduction is implemented throughout the supply chain of SME that manufacture character pillows, doormats, floor mattresses, and scouring pads. This company's supply chain has various issues, including variations in client demand, volatility in the number of products produced, and the company's failure to effectively oversee the supply chain, which results in decreased quality and decreased customer satisfaction. The goal of this study is to use the Failure Mode and Effect Analysis (FMEA) approach to mitigate supply chain risk and develop solutions to minimize or eliminate supply chain risk with the highest RPN and risk score. The risk mitigation approach was employed in this study, with three stages: risk identification, evaluation, and risk analysis, as well as establishing a risk mitigation strategy. The FMEA approach of risk mitigation yielded the three highest RPN (Risk Priority Number) values of the 31 supply chain concerns. These three dangers are inaccuracies in the number of products produced, consumer complaints against companies, and rapid changes in production orders. Our findings theoretically highlight the risks that arise in SME supply chain operations, such as planning, sourcing, manufacturing, delivery, and return. Meanwhile, organizations can use the research findings to coordinate their supply chain plans.